Improved Post remission survival of non- favorable risk Acute Myelogenous Leukemia (AML) patients following initial remission induction therapy with FLAG+/-Idarubicin versus 3 + 7 (Anthracycline + Cytarabine). (June 2020) - Solh, Melhem M; Solomon, Scott R.; Morris, Lawrence E.; Zhang, Xu; Holland, H. Kent; Bashey, Asad
Highlights: FLAG+/- Ida results in higher CR rates compared to 7 + 3. FLAG-Ida results in shorter time to CR and time to transplant compared to 7 + 3. Post remission OS and DFS are better after achieving CR from FLAG-Ida compared to 7 + 3. Abstract: The fludarabine, high dose cytarabine and G-CSF with or without idarubicin combination regimen, referred to as FLAG+/-Ida, is commonly used as a salvage regimen for relapsed/refractory AML but its use as initial induction therapy has been more limited. The impact of choice of induction regimen on post remission survival remains unclear. We retrospectively analyzed 304 consecutive AML patients, with non-favorable NCCN risk who received initial treatment at our center with either 7 + 3 (n = 86) or FLAG+/-Ida (n = 218). Patients in the FLAG+/-Ida group were more likely to achieve remission after one course of induction (74 % vs 62 %, p < 0.001) and had a faster time to achieve CR (30 days vs 37.5, p < 0.001) compared to 7 + 3. The time from diagnosis to transplant was shorter among CR patients after FLAG+/-Ida compared to 7 + 3 (115 vs. 151 days, p < 0.003). The 3-year post-remission OS and DFS was significantly better for patients receiving FLAG-Ida at 54 % and 49 % compared to 39 % and 32 % for 7 + 3 respectively (P = 0.01). Factors associated with post-remission survival included age at CR1, NCCN risk, induction regimen (FLAG+/-Ida vs 3 + 7 h 0.62, p = 0.01) and receipt of HCT. Our data, with the limitations inherent to a retrospective analysis, shows that achieving CR after FLAG+/-Ida has better post remission survival than 7 + 3.